Postantifungal-like effect of sublethal treatment of Candida albicans with acid-electrolyzed water. Issue 3 (March 2015) - Mokudai, Takayuki; Kanno, Taro; Niwano, Yoshimi
Highlights Dilute acid electrolyzed water (AEW) exerted postantifungal like effect. The fungal growth delay caused by dilute AEW is due to reactive oxygen species. The hydroxyl radical is formed from intracellular hypochlorous acid. Partially inactivated AEW could be used for the treatment of oral candidiasis.